2014
DOI: 10.1021/pr500629t
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fingerprint of Dimethyl Sulfone (DMSO2) in Microbial–Mammalian Co-metabolism

Abstract: There is growing awareness that intestinal microbiota alters the energy harvesting capacity of the host and regulates metabolism. It has been postulated that intestinal microbiota are able to degrade unabsorbed dietary components and transform xenobiotic compounds. The resulting microbial metabolites derived from the gastrointestinal tract can potentially enter the circulation system, which, in turn, affects host metabolism. Yet, the metabolic capacity of intestinal microbiota and its interaction with mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 186 publications
2
57
0
Order By: Relevance
“…Breast-fed infants had significantly higher acetate, acetone, formate, glutamine, methanol, proline and myo-inositol. In contrast, formula-fed infants had higher urea, creatine, essential amino acids (threonine and valine) and their amino acid catabolism by-products (2-hydroxybutyrate and 3-hydroxyisobutyrate), choline, and the host-microbial co-metabolite dimethyl sulfone 15 (Table 1). There were no significant differences in the overall composition or individual metabolite concentrations between formula-fed infants assigned to the lactose- or CSS-based formula at baseline (one-way ANOVA followed by post-hoc Tukey HSD test, data not shown), although a weak average effect size of 0.45 for all measured metabolites at baseline (semi-fasted state) between infants fed CSS and infants fed lactose-based formula was observed.
Figure 1Principal components analysis (PCA) reveals differences between breastfed and formula-fed infants at baseline and after feeding.
…”
Section: Resultsmentioning
confidence: 99%
“…Breast-fed infants had significantly higher acetate, acetone, formate, glutamine, methanol, proline and myo-inositol. In contrast, formula-fed infants had higher urea, creatine, essential amino acids (threonine and valine) and their amino acid catabolism by-products (2-hydroxybutyrate and 3-hydroxyisobutyrate), choline, and the host-microbial co-metabolite dimethyl sulfone 15 (Table 1). There were no significant differences in the overall composition or individual metabolite concentrations between formula-fed infants assigned to the lactose- or CSS-based formula at baseline (one-way ANOVA followed by post-hoc Tukey HSD test, data not shown), although a weak average effect size of 0.45 for all measured metabolites at baseline (semi-fasted state) between infants fed CSS and infants fed lactose-based formula was observed.
Figure 1Principal components analysis (PCA) reveals differences between breastfed and formula-fed infants at baseline and after feeding.
…”
Section: Resultsmentioning
confidence: 99%
“…Little is known regarding DMSO2, but a recent study showed an impressive increase in DMSO2 concentrations in obese subjects after several bariatric procedures [62], which have been shown to produce significant improvements in obesity and hypertension, partly due to changes in the microbiota composition [63,64]. Interestingly, DMSO2 may derive from microbial metabolism of methionine [65], thereby reflecting a change in the gut microbiome composition. Consistently, we found a positive correlation between DMSO2 and Bacteroidaceae, both increased after hesperidin supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Destabilising the meniscus showed none of the above features except a reduction in creatine and elevation in dimethylsulfone (DMSO 2 ) 42 . Interestingly DMSO 2 is a metabolite of gastrointestinal bacteria, suggesting a link between the gut microbiome and OA 43 . Proteoglycan destruction at the cleavage sites could liberate glutamine, suggesting a mechanism to increase levels.…”
Section: Plasma Serum and Urine Studiesmentioning
confidence: 99%